Foliar Endophytic Fungi from Geum peckii in Canada - Sarah Adams; Allison Walker; Brent Robicheau; Robin Browne; Diane LaRue (Borealis, 2024)
Foliar fungal endophytes isolated from rare and endangered Eastern Mountain Avens, Geum peckii from Canadian population on Digby Neck, NS. Sampled locations represented varying levels of observable changes to habitat conditions, varying from a minimally changed reference site to heavily changed sites. Reported species are the first known records from this species.